Composite solid electrolyte and its preparation method and application

By coating defective materials of inorganic fast ion conductor nanoparticles in the composite solid electrolyte, and combining ethylene-containing segment polymers and lithium salts, the safety hazards of traditional lithium-ion battery liquid electrolytes and the low ion conductivity problems of composite solid electrolytes are solved, thereby achieving efficient and safe lithium-ion battery electrolytes.

CN115395086BActive Publication Date: 2025-04-25REPT BATTERO ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211000561.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-19
Publication Date
2025-04-25
Estimated Expiration
2042-08-19

AI Technical Summary

Technical Problem

The liquid electrolyte of traditional lithium-ion batteries has safety hazards, such as lithium dendrites' growth, liquid leakage and flammability, and the electrochemical performance becomes worse at high temperatures. The composite solid electrolyte has a low ionic conductivity, which limits its application value in lithium-ion batteries.

Method used

In situ composite method is used to coat defective materials of inorganic fast ion conductor nanoparticles, and combine them with ethylene oxide-containing segment polymers and lithium salts to prepare composite solid electrolytes with high ionic conductivity.

Benefits of technology

It improves the ionic conductivity and mechanical properties of the composite solid electrolyte, enhances the electrochemical performance, reduces the growth of lithium dendrites, and improves the safety and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115395086B_ABST
    Figure CN115395086B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite solid electrolyte and its preparation method and application. The composite solid electrolyte comprises an inorganic solid electrolyte, a polymer containing ethylene oxide segments and a lithium salt. The inorganic solid electrolyte is composed of inorganic fast ion conductor nanoparticles and defective materials coated on the surface of the inorganic fast ion conductor nanoparticles. The composite solid electrolyte has excellent mechanical strength, certain flexibility, and high ionic conductivity. The composite solid electrolyte prepared by the present invention has a high discharge capacity after being assembled into a battery and a high capacity recovery rate after high current charge and discharge, showing excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte and a preparation method thereof, as well as an application of the composite solid electrolyte based on a solid lithium metal battery. Background Art

[0002] Lithium-ion batteries are an indispensable part of the new energy sector. They have outstanding advantages such as long cycle life, high energy density, low self-discharge rate, no memory effect and green environmental protection. They have been widely used in portable mobile electronic devices and have developed into a power source for hybrid electric vehicles (HEV) and electric vehicles (EV). At present, more stringent requirements have been put forward for them, such as higher energy density (such as 350Wh / kg), high power density and safety performance. However, there is a hidden danger that cannot be ignored in the application of traditional lithium-ion batteries in new energy vehicles - liquid electrolyte, which is easy to cause the growth of lithium dendrites when it comes into contact with the lithium anode, and there are also dangers such as leakage and flammability during use; and when used at temperatures above 50°C, the electrochemical performance deteriorates.

[0003] In contrast, inorganic solid electrolytes can solve the above problems very well. Studies have found that inorganic solid electrolytes have the following advantages: 1) good mechanical properties, 2) high thermal stability, 3) excellent chemical and thermochemical stability, 4) flame retardancy. However, inorganic solid electrolytes also have shortcomings, such as lack of flexibility and poor plasticity. Polymer electrolytes have excellent flexibility and are easy to process and shape, which can make up for the shortcomings of inorganic solid electrolytes. Polyethylene oxide-based polymer electrolytes are the most widely studied all-solid-state electrolytes. The ethylene oxide units in polyethylene oxide have high chain flexibility, which is beneficial to Li + conduction, and also has a higher dielectric constant and stronger Li + Solvation ability. The oxygen atoms in the polymer molecular chain have two lone pairs of electrons and have strong coordination ability. However, its low ionic conductivity and low oxidation potential window make it a great obstacle in practical battery applications.

[0004] Composite solid electrolytes have the characteristics of both inorganic and polymer electrolytes, and have a wide electrochemical window, good stability to lithium, good flexibility, and the ability to inhibit lithium dendrites. They can be used as the core component of all-solid-state secondary lithium-ion batteries. However, compared with the ionic conductivity of current commercial electrolytes (10 -3 s / cm), there is still a certain gap between composite solid electrolytes and most research data remain at 10 -5 s / cm stage. Therefore, improving the ionic conductivity of composite solid electrolytes is the only way to improve their application value. Summary of the invention

[0005] The purpose of the present invention is to provide a composite solid electrolyte with high ionic conductivity and a preparation method and application thereof, in view of the problems of current lithium electronic battery electrolyte safety and conventional solid electrolytes.

[0006] The purpose of the present invention can be achieved by the following scheme:

[0007] In a first aspect, the present invention provides a composite solid electrolyte comprising an inorganic solid electrolyte, a polymer containing ethylene oxide segments and a lithium salt, wherein the inorganic solid electrolyte is composed of inorganic fast ion conductor nanoparticles and defective materials coated on the surface of the inorganic fast ion conductor nanoparticles.

[0008] As one embodiment of the present invention, the size of the inorganic fast ion conductor nanoparticles is 60 to 120 nm.

[0009] As an embodiment of the present invention, the inorganic fast ion conductor nanoparticles are one or more of lithium aluminate nanoparticles, garnet-type inorganic fast ion conductors, and perovskite-type inorganic fast ion conductors.

[0010] As an embodiment of the present invention, the defective material is reduced carbon nitride.

[0011] As an embodiment of the present invention, the polymer containing ethylene oxide chain segments is one or more of polyethylene oxide, polyacrylic acid, polyvinylidene fluoride, and polymethyl methacrylate.

[0012] As an embodiment of the present invention, the lithium salt is lithium bis(trifluorosulfonyl)imide.

[0013] In a second aspect, the present invention provides a method for preparing a composite solid electrolyte, comprising:

[0014] S1: preparing a dispersion containing inorganic fast ion conductor nanoparticles and nitrogen-containing compounds;

[0015] S2: lowering the temperature to allow the nitrogen-containing compound to precipitate on the surface of the inorganic fast ion conductor nanoparticles;

[0016] S3: drying the separated precipitate, and then calcining it in an oxygen atmosphere to obtain a precursor;

[0017] S4: adding a reducing metal to the precursor obtained in S3, and heating the mixture of the precursor and the reducing metal under the protection of an inert gas to perform a reduction reaction to obtain inorganic fast ion conductor nanoparticles wrapped by defective materials;

[0018] S5: Inorganic fast ion conductor nanoparticles wrapped with defective materials, polymers containing ethylene oxide segments and lithium salts are prepared into a mixed slurry, which is injection molded and dried to obtain a composite solid electrolyte.

[0019] As an embodiment of the present invention, in step S1, the weight ratio of the inorganic fast ion conductor nanoparticles to the nitrogen-containing compound in the dispersion is 5 to 7:1.

[0020] As an embodiment of the present invention, the nitrogen-containing compound includes one or more of melamine, urea and thiourea.

[0021] As an embodiment of the present invention, in step S2, lowering the temperature is to lower the temperature to 5-10°C.

[0022] As an embodiment of the present invention, in step S3, the oxygen atmosphere used for calcination is an air atmosphere.

[0023] As an embodiment of the present invention, in step S3, the calcination temperature is 350-550°C.

[0024] As an embodiment of the present invention, in step S4, the heating rate of heating the mixture of the precursor and the reducing metal is 2°C-5°C / min.

[0025] As an embodiment of the present invention, in step S4, the weight ratio of the precursor to the reducing metal is 0.8 to 1.2:1.

[0026] As an embodiment of the present invention, in step S4, the temperature of the reduction reaction is 600-1100°C.

[0027] As an embodiment of the present invention, in step S4, the reducing metal is at least one of metal magnesium, metal aluminum, and metal zinc.

[0028] As an embodiment of the present invention, in step S5, drying includes drying in air at room temperature and vacuum drying, and the temperature of vacuum drying is 60-80°C, preferably 70°C.

[0029] As an embodiment of the present invention, in step S5, the weight ratio of the inorganic fast ion conductor nanoparticles wrapped by the defective material to the polymer containing ethylene oxide segments is 1:10-20.

[0030] In a third aspect, the present invention provides the use of a composite solid electrolyte as a battery separator or electrolyte.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The present invention adopts an in-situ composite method to coat the defective material with an inorganic fast ion conductor, and then integrates the polymer containing ethylene oxide segments to prepare a composite solid electrolyte, which makes up for the shortcomings of a single inorganic solid electrolyte or an organic polymer electrolyte. At the same time, compared with liquid electrolytes, the composite solid electrolyte prepared by the present invention has greatly improved safety, has the advantages of being green, low-cost, and time-saving, is conducive to large-scale production, and has great prospects in the application of solid-state batteries.

[0033] (2) The composite solid electrolyte prepared by the present invention, on the one hand, expands the migration path of ions, accelerates the transmission of ions, and has high ionic conductivity. On the other hand, it has suitable mechanical properties, which not only maintains mechanical strength and inhibits the growth of lithium dendrites, but also has a certain degree of flexibility, relieves the pressure of the internal contact interface of the components, effectively improves the deformation of the material, and is beneficial to the electrochemical activity and performance of the material.

[0034] (3) The composite solid electrolyte prepared by the present invention has a high discharge capacity after being assembled into a battery, as well as a high capacity recovery rate after high current charge and discharge, showing excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0036] Figure 1 This is a scanning electron microscope image (SEM) of the composite solid electrolyte prepared in Example 1 of the present invention;

[0037] Figure 2 The figure is a rate charge and discharge curve diagram of the composite solid electrolyte prepared in Example 1 as the electrolyte of a lithium ion battery. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operating processes, which will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0039] The composite solid electrolyte provided by the present invention comprises an inorganic solid electrolyte, a polymer containing ethylene oxide segments and a lithium salt, wherein the inorganic solid electrolyte is composed of inorganic fast ion conductor nanoparticles and defective materials coated on the surface of the inorganic fast ion conductor nanoparticles.

[0040] The present invention coats the defective material on the surface of inorganic fast ion conductor nanoparticles, and prepares a composite solid electrolyte with a polymer containing ethylene oxide segments and a lithium salt. The inorganic fast ion conductor and the defective material with abundant polar bonds provide a dual channel for the transmission of lithium ions, thereby ensuring that the composite solid electrolyte has high ionic conductivity. The introduction of the polymer containing ethylene oxide segments greatly improves the flexibility and plasticity of the composite solid electrolyte, making it easy to process and shape.

[0041] The present invention finds that if defective materials and inorganic fast ion conductors are each simply mixed with polymers containing ethylene oxide segments and lithium salts, for example, inorganic solid electrolytes such as lithium aluminate, boehmite, and reduced nitrogen carbon are mixed with polymers containing ethylene oxide segments and lithium salts, the resulting product ion conductivity is too low to meet the electrical performance requirements. The present invention also finds that defective materials with a pomegranate-like silicon base as a skeleton are not suitable for use as composite solid electrolytes due to their low ion conductivity. It is speculated that this is because silicon is a semiconductor and therefore has a relatively low conductivity.

[0042] As an embodiment of the present invention, the inorganic fast ion conductor nanoparticles are one or more of lithium aluminate nanoparticles, garnet-type inorganic fast ion conductors, and perovskite-type inorganic fast ion conductors.

[0043] It should be noted that the garnet-type inorganic fast ion conductor and the perovskite-type inorganic fast ion conductor in the present invention are lithium lanthanum zirconium oxide lithium ion conductors with a garnet structure or a perovskite structure commonly found in the art.

[0044] Furthermore, the inorganic fast ion conductor nanoparticles are preferably lithium aluminate nanoparticles, and the size of lithium aluminate nanoparticles is preferably 60 to 120 nm. Too small particles have too large surface energy and are prone to agglomeration, which is not conducive to dispersion in the solution; more preferably, the size is 70 nm to 100 nm.

[0045] As an embodiment of the present invention, the defective material is selected from reduced carbon nitride. Reduced carbon nitride has a high specific surface area and a rich internal cavity structure. While increasing the contact area between the electrolyte and the electrode, it can also shorten the diffusion distance of lithium ions and promote the entry of lithium ions. The cavity structure provides a spatial site for the entry of polymers containing ethylene oxide segments, reduces the hole phenomenon, and improves the uniformity of the overall formation of the electrolyte; at the same time, the defects can enhance the lithium storage capacity, which is beneficial to improving the electrochemical activity and energy density of the composite solid electrolyte.

[0046] As an embodiment of the present invention, the polymer containing ethylene oxide segments is one or more of polyethylene oxide, polyacrylic acid, polyvinylidene fluoride, and polymethyl methacrylate; and the lithium salt is lithium bis(trifluorosulfonyl)imide. The present invention uses 60-120nm lithium aluminate nanoparticles as inorganic fast ion conductors and reductive carbon nitride as defective materials. The composite solid electrolyte prepared thereby has a discharge capacity of up to 154.5mAh / g. After high current charge and discharge, the capacity can be restored to about 99.5% of the initial capacity, showing excellent rate characteristics.

[0047] The present invention also provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0048] S1: preparing a dispersion containing inorganic fast ion conductor nanoparticles and nitrogen-containing compounds;

[0049] S2: lowering the temperature to allow the nitrogen-containing compound to precipitate on the surface of the inorganic fast ion conductor nanoparticles;

[0050] S3: drying the separated precipitate, and then calcining it in an oxygen atmosphere to obtain a precursor;

[0051] S4: adding a reducing metal to the precursor obtained in S3, and heating the mixture of the precursor and the reducing metal under the protection of an inert gas to perform a reduction reaction to obtain inorganic fast ion conductor nanoparticles wrapped by defective materials;

[0052] S5: Inorganic fast ion conductor nanoparticles wrapped with defective materials, polymers containing ethylene oxide segments and lithium salts are prepared into a mixed slurry, which is injection molded and dried to obtain a composite solid electrolyte.

[0053] The preparation method first prepares a dispersion liquid in which inorganic fast ion conductor nanoparticles and nitrogen-containing compounds coexist, and allows the nitrogen-containing compounds to be uniformly precipitated on the surface of the inorganic fast ion conductor nanoparticles to obtain a nano precursor, which is then dried and calcined in air at a low temperature to chemically decompose the nitrogen-containing compounds to obtain inorganic fast ion conductor nanoparticles coated with nitrogen-rich carbon nitride materials; then, the nitrogen content can be reduced through a metal thermal reduction reaction, so that the carbon nitride material forms a defective material, increases polar bonds, and is beneficial to the transmission of ions; finally, it is combined with an ethylene oxide segment-containing polymer and a lithium salt to form a composite solid electrolyte, which has the advantages of being green, low-cost, and low-time, and is conducive to large-scale production.

[0054] As an embodiment of the present invention, in step S1, the solvent of the dispersion liquid in which inorganic fast ion conductor nanoparticles and nitrogen-containing compounds coexist is at least one of deionized water, distilled water, and tap water. When preparing the dispersion liquid in which inorganic fast ion conductor nanoparticles and nitrogen-containing compounds coexist, ultrasonic dispersion is first performed, and then water bath magnetic stirring is performed. The ultrasonic dispersion time is controlled to be 2 to 4 hours, and the speed of water bath magnetic stirring is 300 to 500 r / min. The water bath temperature is 60 to 80°C, and the water bath magnetic stirring time is 1 to 3 hours.

[0055] As an embodiment of the present invention, in step S1, the weight ratio of inorganic fast ion conductor nanoparticles and nitrogen-containing compounds in the dispersion is 5 to 7:1, for example, 5:1, 5.5:1, 6:1, 6.5:1 or 7:1, but not limited to the listed values. When the weight ratio is greater than 7:1, the amount of nitrogen-containing compounds precipitated on the surface of lithium aluminate will be small, and it will not be completely wrapped, and the coating layer is thin, and it will be severely lost after subsequent calcination, and the target precursor cannot be obtained; when the weight ratio is less than 5:1, the coating layer will be relatively thick, and the outermost precipitated part is likely to fall off, and the thicker the coating layer, the more unevenly the various parts are heated during the calcination process, resulting in poor consistency of the target precursor.

[0056] As an embodiment of the present invention, in step S2, the temperature is lowered so that the temperature at which the nitrogen-containing compound is precipitated on the surface of the inorganic fast ion conductor nanoparticles is controlled at 5-10°C.

[0057] As an embodiment of the present invention, in step S2, the temperature is lowered to allow the nitrogen-containing compound to precipitate on the surface of the inorganic fast ion conductor nanoparticles, and then the precipitate is separated by centrifugation, wherein the centrifugal speed is controlled to be 3000-5000 r / min, the centrifugal time is 10-15 min, and the number of centrifugation is 3-5 times.

[0058] As an embodiment of the present invention, in step S3, the calcination temperature is 350-550°C, for example, 350°C, 370°C, 400°C, 420°C, 450°C, 470°C, 500°C, 530°C or 550°C, but not limited to the listed values; the oxygen atmosphere used for calcination is air, and the calcination time is 1-4h. When the calcination temperature is too low, no matter how long the calcination time is, the nitrogen-containing compound cannot be completely decomposed, and agglomerates appear; when the calcination temperature is too high, a long calcination time will cause impurities to be generated on the surface of pure inorganic fast ion conductor nanoparticles; a short calcination time will lead to incomplete decomposition of the nitrogen-containing compound. In step S3, vacuum drying is used when drying the separated precipitate, and the vacuum drying temperature is controlled at 60-80°C, and the vacuum drying time is 8-12h. If the vacuum drying temperature is too low, the experimental time will be prolonged. According to the habit of those skilled in the art, it is generally controlled at 60-80°C.

[0059] As an embodiment of the present invention, in step S4, the weight ratio of the precursor to the reducing metal is 0.8 to 1.2:1, for example, it can be 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, 1.15:1 or 1.2:1, but is not limited to the listed values; the temperature of the reduction reaction is 600 to 1100°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, but is not limited to the listed values; the heating rate of heating the mixture of the precursor and the reducing metal is 2°C-5°C / min, and the heating reduction time is 1 to 9h. If the weight ratio of the precursor to the reducing metal is too high, the reduction will be incomplete, resulting in poor structural consistency and weak polarity of the defective material; if the weight ratio is too low, a large amount of nitrogen will be missing in the negative electrode material, affecting the material performance and causing waste of reducing metal. If the temperature of the reduction reaction is too high, the structure of the target product will be severely damaged, and the loss of nitrogen will be too much, resulting in a reduction in the number of polar bonds; if the temperature of the reduction reaction is too low, the degree of reduction is insufficient and the target product cannot be obtained; the reduction temperature is preferably 700-900°C, and the reduction time is preferably 3-7h. If the heating rate is too fast, the defective material will not be completely formed and have poor structural consistency; if the heating rate is too slow, it will easily cause the reduction product by-products to remain, which is not conducive to obtaining the target product-inorganic fast ion conductor nanoparticles wrapped in defective materials.

[0060] As an embodiment of the present invention, the reducing metal in step S4 is at least one of metal magnesium, metal aluminum and metal zinc. During the reduction reaction, an inert gas protection is used, such as argon, helium or nitrogen.

[0061] As an embodiment of the present invention, the mixed slurry is first dried at room temperature after injection molding, and then vacuum dried. The room temperature drying temperature is 25-30°C, and the time is 1-3 hours; the vacuum drying temperature is 60-80°C, and the time is 8-12 hours. If the vacuum drying temperature is too high, the composite solid electrolyte membrane will have defects such as bubbles, cracks, and wrinkles; if the vacuum drying temperature is too low, the composite solid electrolyte membrane will dry slowly, which will make the drying time too long.

[0062] The technical solution of the present invention is described in detail below through specific embodiments.

[0063] Example 1

[0064] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0065] 1) Lithium aluminate nanoparticles and melamine were added to 30 mL of deionized water in a weight ratio of 6:1 and ultrasonically dispersed for 3 h, and then magnetically stirred in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 Uniform dispersion; magnetic stirring speed is 300r / min, water bath temperature is 60℃, and water bath magnetic stirring time is 1h;

[0066] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5 times), and the centrifugal product is vacuum dried at 70° C. for 10 h, and then placed in a tubular furnace for calcination, the calcination atmosphere is air, the calcination temperature is 550° C., and the calcination time is 4 h to obtain a precursor;

[0067] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 1:1 and placed in a tube furnace. The temperature was raised to 750°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 5 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry;

[0068] 4) The product prepared in step 3) was mixed with polyethylene oxide (Shanghai McLean, AR, M W =1×10 6 ) and lithium bis(trifluorosulfonyl imide) (Shanghai McLean, AR, M W =1×10 6 ) are mixed in acetonitrile in a weight ratio of 1:20:1 and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature, the room temperature drying temperature is 25-30°C; the drying time is 3 hours, and then transferred to a 60°C vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0069] The test structure is stainless steel sheet / composite electrolyte membrane / stainless steel sheet and the most classic AC impedance method, with a frequency range of 10 -2 -10 6 Hz, AC signal amplitude Z is 10 -2 V, and the ionic conductivity of the target composite solid electrolyte was calculated.

[0070] The composite solid electrolyte prepared in this embodiment was assembled into a battery and tested: metallic lithium was used as the negative electrode, lithium iron phosphate material was used as the positive electrode, the composite solid electrolyte prepared in this embodiment was used as the diaphragm and the electrolyte, and the battery was assembled in a glove box filled with argon gas, and a charge and discharge test was performed. The charge and discharge curves are shown in FIG. Figure 2As shown in the constant current charge and discharge test (current density 0.1C ~ 1.0C, voltage range 2.5 ~ 4.0V), it can be seen from the figure that the discharge capacity can reach 154.5mAh / g. After high current charge and discharge, the capacity can be restored to about 99.5% of the initial capacity, showing excellent electrochemical performance.

[0071] Example 2

[0072] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0073] 1) Add lithium aluminate nanoparticles and melamine in a weight ratio of 6:1 into 30 mL of deionized water and ultrasonically disperse for 3 h, and stir magnetically in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 The magnetic stirring speed is 300r / min, the water bath temperature is 60℃, and the water bath magnetic stirring time is 1h;

[0074] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5 times), and the centrifugal product is vacuum dried at 70° C. for 10 h, and calcined in a tubular furnace, the calcination atmosphere is air, the calcination temperature is 550° C., and the calcination holding time is 4 h to obtain a precursor;

[0075] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 0.9:1 and placed in a tube furnace. The temperature was raised to 750°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 5 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry;

[0076] 4) mixing the product prepared in step 3) with polyethylene oxide and lithium bis(trifluorosulfonyl)imide in a weight ratio of 1:20:1 in acetonitrile and stirring for 10 hours to dissolve, pouring into a polytetrafluoroethylene mold and drying at room temperature for 3 hours, transferring to a 60° C. vacuum drying oven and drying for 8 hours to obtain the target composite solid electrolyte;

[0077] The test structure is stainless steel sheet / composite electrolyte membrane / stainless steel sheet and the most classic AC impedance method, with a frequency range of 10 -2 -10 6 Hz, AC signal amplitude Z is 10 -2 V, and the ionic conductivity of the target composite solid electrolyte was calculated.

[0078] The composite solid electrolyte prepared in this example was assembled into a battery and tested:

[0079] With lithium metal as the negative electrode, lithium iron phosphate material as the positive electrode, and the composite solid electrolyte prepared in this embodiment as the diaphragm and electrolyte, the battery was assembled in a glove box filled with argon gas and the charge and discharge test was carried out. In the constant current charge and discharge test (current density 0.1C~1.0C, voltage range 2.5~4.0V), the discharge capacity can reach 150.3mAh / g. After high current charge and discharge, the capacity can be restored to about 94.7% of the initial capacity.

[0080] Example 3

[0081] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0082] 1) Add lithium aluminate nanoparticles and melamine in a weight ratio of 6:1 into 30 mL of deionized water for ultrasonic dispersion for 3 h, and stir magnetically in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 The magnetic stirring speed is 300r / min, the water bath temperature is 60℃, and the water bath magnetic stirring time is 1h;

[0083] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5 times), and the centrifugal product is vacuum dried at 70° C. for 10 h, and calcined in a tubular furnace, the calcination atmosphere is air, the calcination temperature is 550° C., and the calcination holding time is 4 h to obtain a precursor;

[0084] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 1.1:1 and placed in a tube furnace. The temperature was raised to 750°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 5 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry;

[0085] 4) mixing the product prepared in step 3) with polyethylene oxide and lithium bis(trifluorosulfonyl)imide in a weight ratio of 1:20:1 in acetonitrile and stirring for 10 hours to dissolve, pouring into a polytetrafluoroethylene mold and drying at room temperature for 3 hours, transferring to a 60° C. vacuum drying oven and drying for 8 hours to obtain the target composite solid electrolyte;

[0086] The test structure of stainless steel sheet / composite electrolyte membrane / stainless steel sheet and the most classic AC impedance method are used, with a frequency range of 10 -2 -10 6 Hz, AC signal amplitude Z is 10 -2V, and the ionic conductivity of the target composite solid electrolyte was calculated.

[0087] The composite solid electrolyte prepared in this example was assembled into a battery and tested:

[0088] With lithium metal as the negative electrode, lithium iron phosphate material as the positive electrode, and the composite solid electrolyte prepared in this embodiment as the diaphragm and electrolyte, the battery was assembled in a glove box filled with argon gas and the charge and discharge test was carried out. In the constant current charge and discharge test (current density 0.1C~1.0C, voltage range 2.5~4.0V), the discharge capacity can reach 149.8mAh / g. After high current charge and discharge, the capacity can be restored to about 93.1% of the initial capacity.

[0089] Example 4

[0090] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0091] 1) Lithium aluminate nanoparticles and melamine were added to 30 mL of deionized water in a weight ratio of 6:1 and ultrasonically dispersed for 3 h, and then magnetically stirred in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 The magnetic stirring speed is 300r / min, the water bath temperature is 60℃, and the water bath magnetic stirring time is 1h;

[0092] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5 times), and the centrifugal product is vacuum dried at 70° C. for 10 h, and calcined in a tubular furnace, the calcination atmosphere is air, the calcination temperature is 550° C., and the calcination time is 4 h, to obtain a precursor;

[0093] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 1:1 and placed in a tube furnace. The temperature was raised to 1050°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 5 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry.

[0094] 4) The product prepared in step 3) was mixed with polyethylene oxide and lithium bis(trifluorosulfonyl)imide in a weight ratio of 1:20:1 in acetonitrile and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0095] The composite solid electrolyte prepared in this example was assembled into a battery and tested:

[0096] With lithium metal as the negative electrode, lithium iron phosphate material as the positive electrode, and the composite solid electrolyte prepared in this embodiment as the diaphragm and electrolyte, the battery was assembled in a glove box filled with argon gas for charge and discharge tests. In the constant current charge and discharge test (current density 0.1C~1.0C, voltage range 2.5~4.0V), the discharge capacity can reach 148.7mAh / g. After high current charge and discharge, the capacity can be restored to about 92.7% of the initial capacity.

[0097] Example 5

[0098] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0099] 1) Lithium aluminate nanoparticles and melamine were added to 30 mL of deionized water in a weight ratio of 6:1 and ultrasonically dispersed for 3 h, and then magnetically stirred in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 The magnetic stirring speed is 300r / min, the water bath temperature is 60℃, and the water bath magnetic stirring time is 1h;

[0100] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5 times), and the centrifugal product is vacuum dried at 70° C. for 10 h, and calcined in a tubular furnace, the calcination atmosphere is air, the calcination temperature is 550° C., and the calcination time is 4 h, to obtain a precursor;

[0101] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 1:1 and placed in a tube furnace. The temperature was raised to 900°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 6 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry;

[0102] 4) The product prepared in step 3) was mixed with polyethylene oxide and lithium bis(trifluorosulfonyl)imide in a weight ratio of 1:20:1 in acetonitrile and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0103] The composite solid electrolyte prepared in this embodiment was assembled into a battery for testing: with metallic lithium as the negative electrode, lithium iron phosphate material as the positive electrode, and the composite solid electrolyte prepared in this embodiment as the diaphragm and electrolyte, the battery was assembled in a glove box filled with argon gas for charge and discharge testing. In the constant current charge and discharge test (current density 0.1C ~ 1.0C, voltage range 2.5 ~ 4.0V), the discharge capacity can reach 142.7mAh / g. After high current charge and discharge, the capacity can be restored to about 89.7% of the initial capacity.

[0104] Example 6

[0105] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0106] 1) Lithium aluminate nanoparticles and melamine were added to 30 mL of deionized water in a weight ratio of 6:1 and ultrasonically dispersed for 3 h, and then magnetically stirred in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 The magnetic stirring speed is 300r / min, the water bath temperature is 60℃, and the water bath magnetic stirring time is 1h;

[0107] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5), and the centrifugal product is vacuum dried at 70° C. for 10 h, and calcined in a tubular furnace, the calcination atmosphere is air, the calcination temperature is 400° C., and the calcination time is 4 h to obtain a precursor;

[0108] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 1:1 and placed in a tube furnace. The temperature was raised to 750°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 5 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry;

[0109] 4) The product prepared in step 3) was mixed with polyethylene oxide and lithium bis(trifluorosulfonyl)imide in a weight ratio of 1:20:1 in acetonitrile and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0110] The composite solid electrolyte prepared in this embodiment was assembled into a battery for testing: with metallic lithium as the negative electrode, lithium iron phosphate material as the positive electrode, and the composite solid electrolyte prepared in this embodiment as the diaphragm and electrolyte, the battery was assembled in a glove box filled with argon gas for charge and discharge testing. In the constant current charge and discharge test (current density 0.1C~1.0C, voltage range 2.5~4.0V), the discharge capacity can reach 132.1mAh / g, and after high current charge and discharge, the capacity can be restored to about 85.6% of the initial capacity.

[0111] Example 7

[0112] This embodiment provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0113] 1) Lithium aluminate nanoparticles and melamine were added to 30 mL of deionized water in a weight ratio of 6:1 and ultrasonically dispersed for 3 h, and then magnetically stirred in a water bath to obtain a total concentration of lithium aluminate and melamine of 3.3 mol·L -1 The magnetic stirring speed is 300r / min, the water bath temperature is 60℃, and the water bath magnetic stirring time is 1h;

[0114] 2) lowering the temperature of the uniform dispersion prepared in step 1) to 10° C. to precipitate melamine on the surface of lithium aluminate nanoparticles, centrifuging (the centrifugal speed is controlled to be 4000 r / min, the centrifugal time is 12 min, and the number of centrifugations is 5 times), and the centrifugal product is vacuum dried at 70° C. for 10 h, and calcined in a tubular furnace, the calcination atmosphere is air, the calcination temperature is 350° C., and the calcination time is 4 h, to obtain a precursor;

[0115] 3) The precursor prepared in step 2) was mixed with magnesium metal in a weight ratio of 1:1 and placed in a tube furnace. The temperature was raised to 750°C at a heating rate of 2°C / min. Argon was introduced to carry out magnesium thermal reduction reaction. The temperature was kept for 5 hours. The magnesium thermal reduction product was treated with 3 mol·L -1 Soak in hydrochloric acid for 1 hour, wash with deionized water until neutral, and dry.

[0116] 4) The product prepared in step 3) was mixed with polyethylene oxide and lithium bis(trifluorosulfonyl)imide in a weight ratio of 1:10:1 in acetonitrile and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0117] The composite solid electrolyte prepared in this embodiment was assembled into a battery for testing: with metallic lithium as the negative electrode, lithium iron phosphate material as the positive electrode, and the composite solid electrolyte prepared in this embodiment as the diaphragm and electrolyte, the battery was assembled in a glove box filled with argon gas for charge and discharge testing. In the constant current charge and discharge test (current density 0.1C~1.0C, voltage range 2.5~4.0V), the discharge capacity can reach 123.1mAh / g, and after high current charge and discharge, the capacity can be restored to about 80.3% of the initial capacity.

[0118] Example 8

[0119] This embodiment provides a method for preparing a composite solid electrolyte, which is basically the same as the preparation method in Example 1, except that the weight ratio of the precursor to the reducing metal in step 3) is 0.8:1. According to the same assembled battery test method as in Example 1, the first discharge specific capacity is measured to be 138.6 mAh / g, and after high current charge and discharge, the capacity can be restored to about 72.5% of the initial capacity.

[0120] Example 9

[0121] This embodiment provides a method for preparing a composite solid electrolyte, which is basically the same as the preparation method in Example 1, except that the weight ratio of the precursor to the reducing metal in step 3) is 1.2: 1. According to the same assembled battery test method as in Example 1, the first discharge specific capacity is measured to be 132.7 mAh / g, and after high current charge and discharge, the capacity can be restored to about 67.8% of the initial capacity.

[0122] Example 10

[0123] This embodiment provides a method for preparing a composite solid electrolyte, which is basically the same as the preparation method in Example 1, except that the magnesium thermal reduction temperature in step 3) is 650° C. According to the same assembled battery test method as in Example 1, the first discharge specific capacity is measured to be 148.4 mAh / g, and after high current charge and discharge, the capacity can be restored to about 65.3% of the initial capacity.

[0124] Comparative Example 1

[0125] This comparative example provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0126] 1) Lithium aluminate nanoparticles, polyethylene oxide and lithium salt were mixed in acetonitrile in a weight ratio of 1:20:1 and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0127] 2) Using the test structure of stainless steel sheet / composite electrolyte membrane / stainless steel sheet and the most classic AC impedance method, the frequency range is 10 -2 -10 6 Hz, AC signal amplitude Z is 10 -2 V, and the ionic conductivity of the target composite solid electrolyte was calculated.

[0128] Comparative Example 2

[0129] This comparative example provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0130] 1) Boehmite, polyethylene oxide and lithium salt were mixed in acetonitrile in a weight ratio of 1:20:1 and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0131] 2) Using the test structure of stainless steel sheet / composite electrolyte membrane / stainless steel sheet and the most classic AC impedance method, the frequency range is 10 -2 -10 6 Hz, AC signal amplitude Z is 10 -2 V, and the ionic conductivity of the target composite solid electrolyte was calculated.

[0132] Comparative Example 3

[0133] This comparative example provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0134] 1) Unreduced carbon nitride, polyethylene oxide and lithium salt were mixed in acetonitrile in a weight ratio of 1:20:1 and stirred for 10 hours to dissolve, poured into a polytetrafluoroethylene mold and dried at room temperature for 3 hours, and transferred to a 60° C. vacuum drying oven and dried for 8 hours to obtain the target composite solid electrolyte.

[0135] 2) Using the test structure of stainless steel sheet / composite electrolyte membrane / stainless steel sheet and the most classic AC impedance method, the frequency range is 10 -2 -10 6 Hz, AC signal amplitude Z is 10 -2 V, and the ionic conductivity of the target composite solid electrolyte was calculated.

[0136] Table 1 Ionic conductivity of the composite electrolytes obtained in each embodiment and comparative example (60°C)

[0137] example Ionic conductivityσ(s / cm) Example 1 <![CDATA[4.45×10 -4 ]]> Example 2 <![CDATA[1.37×10 -4 ]]> Example 3 <![CDATA[9.17×10 -5 ]]> Comparative Example 1 <![CDATA[5.29×10 -5 ]]> Comparative Example 2 <![CDATA[3.88×10 -5 ]]> Comparative Example 3 <![CDATA[1.58×10 -5 ]]>

[0138] It can be seen from Table 1 that the composite solid electrolyte prepared by the present invention can effectively improve ionic conductivity.

[0139] Comparative Example 4

[0140] This comparative example provides a method for preparing a composite solid electrolyte, which is basically the same as the preparation method in Example 1, except that the calcination temperature in step 2) is 650°C and the time is 4 hours. According to the same assembled battery test method as in Example 1, the first discharge specific capacity is measured to be 149.2 mAh / g, and after high current charge and discharge, the capacity can be restored to about 76.1% of the initial capacity.

[0141] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a composite solid electrolyte, the composite solid electrolyte comprising an inorganic solid electrolyte, a polymer containing ethylene oxide segments and a lithium salt, characterized in that: The inorganic solid electrolyte is composed of inorganic fast ion conductor nanoparticles and defective materials coated on the surface of the inorganic fast ion conductor nanoparticles; The inorganic fast ion conductor nanoparticles are lithium aluminate nanoparticles, and the defective material is reduced carbon nitride; The method comprises: S1: preparing a dispersion containing inorganic fast ion conductor nanoparticles and nitrogen-containing compounds; S2: lowering the temperature to allow the nitrogen-containing compound to precipitate on the surface of the inorganic fast ion conductor nanoparticles; S3: drying the separated precipitate, and then calcining it in an oxygen atmosphere to obtain a precursor; S4: adding a reducing metal to the precursor obtained in S3, and heating the mixture of the precursor and the reducing metal under the protection of an inert gas to perform a reduction reaction to obtain inorganic fast ion conductor nanoparticles wrapped by defective materials; S5: preparing a mixed slurry of inorganic fast ion conductor nanoparticles wrapped by defective materials, polymers containing ethylene oxide segments and lithium salts, injection molding and drying to obtain a composite solid electrolyte; In step S3, the calcination temperature is 350-550°C; In step S4, the weight ratio of the precursor to the reducing metal is 0.9-1.1:

1.

2. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: The polymer containing ethylene oxide chain segments is one or more of polyethylene oxide, polyacrylic acid, polyvinylidene fluoride, and polymethyl methacrylate; and the lithium salt is lithium bis(trifluorosulfonyl)imide.

3. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step S1, the weight ratio of the inorganic fast ion conductor nanoparticles to the nitrogen-containing compound in the dispersion is 5-7:

1.

4. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step S4, the temperature of the reduction reaction is 600-1100°C.

5. The method for preparing a composite solid electrolyte according to claim 3, characterized in that: In step S5, the weight ratio of the inorganic fast ion conductor nanoparticles wrapped by the defective material to the polymer containing ethylene oxide segments is 1:10-20.

6. Use of the composite solid electrolyte prepared by the method for preparing a composite solid electrolyte according to any one of claims 1 to 5 as a battery separator or electrolyte.

Citation Information

Patent Citations

  • Method for preparing organic-inorganic composite solid electrolyte in batch at low cost

    CN110534800A

  • Carbon nitride and carbon coated NASICON type electrode material and preparation method thereof

    CN110880590A

  • Pomegranate-like silicon-based negative electrode material and preparation method thereof

    CN113428865A